Resources Required for Implementation of SARS‐CoV‐2 Screening in Massachusetts K‐12 Public Schools in Winter/Spring 2021. (7th March 2022) - Lee, Stephanie S.; Weitz, Michelle; Ardlie, Kristin; Bantham, Amy; Schuckel, Michele Fronk; Goehringer, Katey; Hogue, Caitlin; Hosking, Rosy; Mortimer, Kathleen; Saadat, Alham; Seaman‐Chandler, Jill; Linas, Benjamin P.; et al.
ABSTRACT: BACKGROUND: The financial costs and human resource requirements at the school and district level to implement a SARS‐CoV‐2 screening program are not well known. METHODS: A consortium of Massachusetts public K‐12 schools was formed to implement and evaluate a range of SARS‐CoV‐2 screening approaches. Participating districts were surveyed weekly about their programs, including: type of assay used, individual vs. pooled screening, approaches to return of results and deconvolution of positive pools, number and type of personnel, and hours spent implementing the screening program, and hours spent on program implementation. RESULTS: In 21 participating districts, over 21 weeks from January to June 2021, the positivity rate was 0.0% to 0.21% among students and 0.0% to 0.13% among educators/staff. The average weekly cost to implement a screening program, including assay and personnel costs, was 17.00 per person tested; this was 46.68 for individual screenings and 15.61 for pooled screenings. The total weekly costs by district ranged from 1, 644 to 93, 486, and districts screened between 58 and 3675 people per week. CONCLUSIONS: Where screening is recommended for the 2021 to 2022 school year due to high COVID‐19 incidence, understanding the human resources and finances required to implement screening will assist district policymakers in planning.